Early Marriage and Implications for Future Orientation in Islamic Law - Rifandanu, Farel; Febrianti, Ayu (Contemporary Issues on Interfaith Law and Society, 2023)
Early marriage, deeply ingrained in cultural and religious traditions like Islam, profoundly influences individuals' future perspectives. This paper delves into early marriage within Islamic law's framework, examining its ramifications on individuals' outlooks. Drawing from Islamic jurisprudence, sociological insights, and psychological perspectives, the study scrutinizes early marriage's legal, social, and psychological dimensions. While Islam sanctifies marriage, it also underscores maturity and readiness, often at odds with prevalent early marriage customs. This practice poses multifaceted implications. Legally, it raises concerns about consent and well-being, especially when parties lack full maturity. Socially, early marriage curtails educational and economic opportunities, hindering future planning and goal pursuit. Psychologically, it induces stress and coping challenges with adult responsibilities prematurely. Additionally, early marriage affects broader societal aspects like population growth and gender equality. Addressing this issue necessitates a holistic approach integrating legal reforms, educational programs, and community support to safeguard vulnerable groups, notably girls and young women. By scrutinizing the legal, social, and psychological facets of early marriage, this paper seeks to inform interventions aligning with Islamic principles and universal human rights, promoting individuals' protection and empowerment.